-3(5t-3)+6t=8t-5

Simple and best practice solution for -3(5t-3)+6t=8t-5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3(5t-3)+6t=8t-5 equation:



-3(5t-3)+6t=8t-5
We move all terms to the left:
-3(5t-3)+6t-(8t-5)=0
We add all the numbers together, and all the variables
6t-3(5t-3)-(8t-5)=0
We multiply parentheses
6t-15t-(8t-5)+9=0
We get rid of parentheses
6t-15t-8t+5+9=0
We add all the numbers together, and all the variables
-17t+14=0
We move all terms containing t to the left, all other terms to the right
-17t=-14
t=-14/-17
t=14/17

See similar equations:

| 2,000(x-0.3)=6,000 | | x2=25361 | | f(-4)=5(-4)-12 | | 8b-8-6b=10 | | 0=-4t^2+16t+48 | | 12x+9=6x+5=9x-2 | | 30=20+2w | | -5+2(-4+3n)=22 | | -7x=-10x+21 | | 2a+3(5a-7)=47 | | -1x=74 | | -8-(5x+3)=-x+7-3x | | 6/5(5−10x)=3x−24 | | 12x+9=6x+5 | | x+7=81 | | 2x+3(5x+7)=55 | | x+16+4x-12+x+10=180 | | (5x+2)+(4x-3=) | | 12y-21=8 | | 3(x+8)=9(x+3) | | −4(−4x+3)=7x-7 | | 3(1-3x)=2(5x+1) | | -11.02+5.1b=7b | | -2(5n-2)-3n+7=154 | | T=2s+16.21 | | 3(x+8)=9(x+3 | | 7x+12=-7+3x | | | | |2x+3|-9=12 | | 1​ x+6=16 | | 33=-8v+3(v+6) | | 5x+13=9x+5 |

Equations solver categories